Rasio Solvabilitas Terhadap Profitabilitas Perusahaan Sektor Agrikultur yang Terdaftar di BEI Periode 2019 - Tine Badriatin; Lucky Radi Rinandiyana; Asep Saepudin (Jurnal Pasar Modal dan Bisnis, 2021)
Every company must have a goal that is to make a profit. To obtain a profit, the company must allocate the amount of funds so that it will be obtained solvency that is optimal enough so that a profit is obtained in accordance with that expected by a company. The purpose of this study was to find out how much solvency ratio affects Profitability in Agricultural Sector Companies Listed in IDX Period 2019. In this study, samples used as many as 15 companies. This study took data in the form of financial statements for the period 2019. Variables in this study consist of free variables namely Return on Equity and bound variables are Debt to Asset Ratio, Debt to Equity Ratio, and Coverage Ratio. Where this research uses multiple linear regression analysis techniques after passing the classic assumption test consisting of hypothetical tests. The results prove that solvency affects profitability.